Faktor-faktor yang Memengaruhi Ketrampilan Digital Karyawan bagi UMKM untuk Naik Kelas - Petrisia, Gusti Made Cahyani; Dwiatmadja, Christantius; Margarena, Agung Novianto; Manoppo, Edward (Jurnal Maksipreneur, 2024)
This research aims to find out how technology adoption factors mediate information compatibility, organizational and environmental factors, and their influence on employee digital skills for MSMEs to advance to class. This research uses a descriptive method using a quantitative approach. Where primary data was obtained by distributing questionnaires via Google forms with a sample of 45 respondents from the total permanent employees at Naruna Keramik Salatiga. This research uses outer relation data analysis techniques or measurement models. The results of this research show that the technology adoption factor mediates the significant influence of information compatibility and organization on digital skills. Technology adoption cannot mediate the significant influence of the environment on digital skills. Information compatibility and organization have a direct influence on digital skills. The environment does not have a direct influence on digital skills.